TEACHERS' CHALLENGES IN ASSESSING SPEAKING SKILLS IN SYNCHRONOUS ONLINE DISCUSSIONS: A CASE STUDY FROM AN INDONESIAN EFL CONTEXT - Sylvia Putri; Sri Wahyuni (ELP (Journal of English Language Pedagogy), 2026)
Synchronous online discussions have become essential for speaking instruction in digital EFL contexts, however evaluating students’ performance in these real-time environments remains challenges. However numerous studies emphasized the significance of digital assessment, only a few concentrated on looking at the specific challenges that teachers face while assessing students' speaking abilities during synchronous online discussions. Furthermore, the objective of this study involves looking into the challenges teachers face and the strategies they use to maintain online speaking assessments fair, reliable, and effective. In collecting the data, this study used a descriptive qualitative approach, structured interviews were conducted with three EFL teachers from the Speaking Partner Course in Pare–Kediri, and data were analyzed by thematic analysis. Findings indicate three significant challenges: technological constraints such as insufficient connectivity, time limitations during online sessions, and authenticity concerns regarding students’ autonomous performance. By using institutional rubrics, conducting pre-assessment technological checks, carefully managing their time, and offering ongoing feedback, teachers were able to address these problems. The study emphasizes the need of strengthening teachers' digital competence and assessment literacy, and it encourages focused professional development and improved institutional support to improve the quality of online speaking assessments.